Marine n-3 long-chain polyunsaturated fatty acid intake in pregnancy and risk of early life infections in three Nordic cohorts: a HEDIMED consortium study - Rantala, Aino K.; Hakola, Leena; Brustad, Nicklas; Tapia, German; Hård af Segerstad, Elin M.; Lehtonen, Jussi; Thorsen, Jonathan; Åkerlund, Mari; Parr, Christine L.; Magnus, Maria C.; Lund-Blix, Nicolai A.; Stokholm, Jakob; et al. (Elsevier BV, 2026)
Background
n-3 long-chain polyunsaturated fatty acids (n-3 LCPUFA) have anti-inflammatory effects that may influence immune-mediated diseases.
Objective
We investigated whether higher maternal pregnancy intake of n-3 LCPUFA is associated with a lower infection incidence in young children.
Methods
We used data from three Nordic cohorts: the Norwegian Mother, Father and Child Cohort study (MoBa, n=76,026), the Finnish Diabetes Prediction and Prevention study (DIPP, n=560) and the Copenhagen Prospective Studies on Asthma in Childhood 2010 cohort (COPSAC2010, n=680). Childhood infections up to age 36 months were assessed using questionnaires in MoBa, coxsackievirus B 1-6 (CVB1-6) neutralizing antibodies in DIPP, and pathogenic viral PCR identification from acute respiratory episodes in COPSAC2010. Maternal n-3 LCPUFA intake was assessed through validated food frequency questionnaires in MoBa and DIPP, while COPSAC2010 used a randomized trial design where pregnant women received fish oil capsules or placebo.
Results
Higher n-3 LCPUFA intake was not significantly associated with lower respiratory tract infection (adjusted incidence rate ratio (aIRR) 0.99; 95% CI 0.94-1.03) but was associated with a reduced risk of upper respiratory tract infections (aIRR 0.99; 95% CI 0.98-0.99) and gastroenteritis (aIRR 0.96; 95% CI 0.95-0.98) per g/day up to age 36 months in MoBa. The DIPP study found no association between n-3 LCPUFA intake and having ≥1 CVB infection (adjusted odds ratio 1.74; 95% CI 0.64-4.72, per g/day). The COPSAC2010 trial found no significant effects of the intervention for pathogen specific respiratory episodes (IRR 0.86; 95% CI 0.69-1.07).
Conclusions
This study does not provide consistent evidence that higher maternal n-3 LCPUFA